Learning Guidance As An Effort To Overcome Learning Difficulties Of Students In Ngawensari Village - Alfina Kusumadewi; Muhammad Aqil Luthfan (Universitas Palangka Raya, 2024)
Various efforts have been made by the government to improve the quality of education in Indonesia both in terms of quality and quantity. This effort is carried out starting from elementary education to tertiary education. Law No. 20 of 2003 on the National Education System states that